ON THE ISSUE OF FORMATION OF IMAGES OF PERSONALITY CONSCIOUSNESS WHEN TEACHING RUSSIAN LANGUAGE AND LITERATURE TO STUDENTS OF NON-LINGUISTIC UNIVERSITIES OF THE REPUBLIC OF UZBEKISTAN (American Journal of Research in Humanities and Social Sciences, 2024)
This article is about revealing the importance of ethnocultural realities in the process of teaching Russian language and literature to students of law schools of the Republic of Uzbekistan.Special attention is paid to revealing the meaning of culturally marked vocabulary by translational and non-translational methods. The author refers to the translation method of semantics as translation-interpretation, in which, in addition to the equivalent in their native language, students are informed about the coincidence or discrepancy in the scope of the meaning of lacunae. We are also talking about a non-translational method of semantics, which includes: demonstration of objects, gestures, actions, paintings, drawings, slides, slides and disclosure of the meanings of realities in Russian, for which definitions can be used - descriptions of the meaning of a new word with already known words.